Influence of increased training on blood glucose, lactate and ammonia level in athletes - Gailiuniene, A.; Sokolova, B.; Liaugminas, A. (Education. Physical training. Sport, 2000)
The aim of our research was to investigate and evaluate glucose, lactate and amonia levels in wrestler`s blood. In wrestlers, the training season program had no significant influence either on heart rate or blood plasma glucose levels. However, a significant drop in the post-exercise plasma ammonia concentration was observed (from 108.7 to 98.9 µmol/l) after the training season. The lactate-glucose and lactate-ammonia relationship after the exhausting exercise, as affected by training, is probably due to the influence of training on hormonal regulation of glucose, lactate and ammonia production. Data of metabolic disturbances in training season of athletes should be remembered when one is trying to interpret and extrapolate data in the training of athletes.